PEMUJAAN AGNI DALAM SAMA WEDA - I Nyoman Suka Ardiyasa; I Nyoman Raka Astrini (Genta Hredaya: Media Informasi Ilmiah Jurusan Brahma Widya STAHN Mpu Kuturan Singaraja, 2020)
One of the Sama Weda holy book isÂ  discuss Agni worship which is believed to be able to destroy sins and be able to provide information or efforts towards success or efforts to obtain art. In the Reg Vedic scriptures, in the first mantram, the first Sukta at the first Mandala Agni is called Purohita the devata which leads to prosperity and happiness. In Sama Weda, Agni is said to be a witness who still exists today in every Hindu worship. Agni is a visible manifestation of God Almighty who is very close to his people who are believed to always give his holy light to help his people in life, where in the implementation of the yajna ceremony conducted by his people Agni is always the witness as an ambassador, chosen, in the organizer of the holy yajna because it is believed Agni who gave all the wealth and protect his people from all suffering.Anggraini, P. M. R., & Somawati, A. V. (2020). PRAMANA DALAM PERSPEKTIF PENALARAN FILSAFATI.Â Genta Hredaya,Â 2(2).Artiningsih, N. W. J. (2020). ESTETIKA HINDU PADA PEMENTASAN TOPENG SIDAKARYA DALAM UPACARA DEWA YADNYA.Â Genta Hredaya,Â 3(2).Dewi, N. M. E. K. (2020). TEOLOGI DALAM PEMUJAAN SIWA LINGGA.Â Genta Hredaya,Â 3(2).Eka Suadnyana, I. B. (2020). IMPLEMENTASI NILAI ETIKA HINDU PADA GEGURITAN NI SUMALA.Â Bawi Ayah: Jurnal Pendidikan Agama Dan Budaya Hindu,Â 11(1), 100-116. https://doi.org/10.33363/ba.v11i1.445Gunawijaya, I. W. T. (2020). TEOLOGI SEKS DALAM PENCIPTAAN KETURUNAN SUPUTRA.Â Genta Hredaya,Â 3(2).Hartaka, I. M. (2020). MEMBANGUN SEMANGAT KEBANGSAAN PERSPEKTIF ETIKA HINDU.Â Genta Hredaya,Â 3(2).Heriyanti, K. (2020). KEUTAMAAN API SEBAGAI SIMBOL DEWA AGNI DALAM AKTIVITAS RITUAL KEAGAMAAN UMAT HINDU.Â JÃ±ÄnasiddhÃ¢nta: Jurnal Teologi Hindu,Â 2(1).Krishna, I. B. W. (2020). KAJIAN MULTIKULTURALISME: IDE-IDE IMAJINER DALAM PEMBANGUNAN PUJA MANDALA.Â Genta Hredaya,Â 3(2).Marselinawati, P. S. (2020). FILSAFAT KETUHANAN DALAM BHAGAVAD GITA.Â Genta Hredaya,Â 3(1).Minsarwati, W. 2002. Mitos Merapi dan Kearifan Ekologi. Kreasi WacanaÂ  : Yogyakarta. Pudja, Gede. 1979. Sama Weda. Departemen Agama RI : Jakarta.Semadi Astra Dkk. 2010. Mutiara Warisan Budaya Sebuah Bunga Rampai Arkeologis. Arkeologi Fakultas Sastra Kerjasama dengan Progran Studi Magister dan Program Doktor Kajian Budaya Universitas Udayana Denpasar. Titib., I Made. 2007. Teologi dan Simbol-Simbol dalam Agama Hindu. Paramitha : Surabaya.Untara, I. M. G. S., & Suardika, I. N. (2020). MAKNA FILOSOFI AJARAN SIWA BUDDHA DALAM LONTAR BUBUKSAH.Â Genta Hredaya,Â 3(1).Windya, I. M. (2020). KAKAWIN ARJUNA WIWÄ€HA: KAJIAN TEOLOGI HINDU.Â Genta Hredaya,Â 3(2).Yhani, Putu Cory Candra. "RELEVANSI AJARAN SOCRATES DALAM AGAMA HINDU."Â Genta HredayaÂ 3.2 (2020).Yogiswari, K. S. (2020).Â Tabu, Perspektif Filsafat Seputar Seksualitas Manusia. Nilacakra.Yogiswari, K. S. (2018). PENDIDIKAN HOLISTIK JIDDU KRISHNAMURTI.Â GUNA WIDYA: JURNAL PENDIDIKAN HINDU,Â 5(1).Suadnyana, I. B. P. E. (2020). AJARAN AGAMA HINDU DALAM GEGURITAN KUNJARAKARNA.Â Genta Hredaya,Â 3(1).